Danger of floating venous thrombosis: myth or reality?. (June 2023) - Chernukha, Larisa; Khrebtiy, Yaroslav; Khrebtii, Halyna
Introduction: To date, the problem of venous thromboembolism and its consequences remains relevant, despite significant progress in the development of phlebology and technologies. Aim: In our study, we tried to assess the "danger" of floating DVTs, methods and features of conservative and surgical treatment of patients with floating DVTs, analyze the results of treatment of this group of patients, and draw conclusions based on our data. Materials and methods: The results of treatment of 1297 patients with venous thromboembolism for the period 2011–2022 were analyzed. 104 patients were treated with floating deep vein thrombosis, 1193 patients had occlusive proximal venous thrombosis. Results: In our study, we determined the danger of floating DVT by comparing the facts of the migration of thrombotic masses in the proximal direction according to the results of treatment in two groups of patients. The first group consisted of 10 patients with proximal floating venous thromboses who were implanted with cava filters, the second group consisted of 28 patients with occlusive proximal venous thrombosis who were implanted with cava filters. Embolism occurred in 40.0% of cases floating DVT, while no cases of embolism were detected in occluding DVT ( p < 0.01). Groups of patients with the length of the floating part of the thrombus up to 5 cm were analyzed. Anticoagulant therapy was used in 42 cases; thrombectomy was performed in 52 cases. There was no case of pulmonary embolism when treated with both conservative and surgical methods. Conclusions: Based on our research, it can be stated that floating thrombosis of deep veins of proximal venous segments is a type of thrombosis that has an increased risk of thromboembolic complications when the length of the floating part is 5 cm or more.